2019
DOI: 10.5223/pghn.2019.22.4.377
|View full text |Cite
|
Sign up to set email alerts
|

Same-Day versus Overnight Observation after Outpatient Pediatric Percutaneous Liver Biopsy: A Retrospective Cohort Study

Abstract: Purpose Percutaneous liver biopsy (PLB), a diagnostic procedure to identify several hepatobiliary disorders, is considered safe with low incidence of associated complications. While postoperative monitoring guidelines are suggested for adults, selection of procedural recovery time for children remains at the discretion of individual operators. We aim to determine if differences exist in frequency of surgical complications, unplanned admissions, and healthcare cost for children undergoing outpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The cost reduction would have been larger had the PACU indirect expenses included in the calculation. Kozlovich et al (17) concluded that embracing a shorter observation period following PLB as standard practice for children without major comorbidities can potentially lead to substantial positive economic impact. Similar observation was reported with a 1-hour observation that resulted in reduced facility fee cost, mainly related to decrease in nursing staff utilization with potential for significant cost savings and more efficient use of facility, space, and nursing staff (13).…”
Section: Discussionmentioning
confidence: 99%
“…The cost reduction would have been larger had the PACU indirect expenses included in the calculation. Kozlovich et al (17) concluded that embracing a shorter observation period following PLB as standard practice for children without major comorbidities can potentially lead to substantial positive economic impact. Similar observation was reported with a 1-hour observation that resulted in reduced facility fee cost, mainly related to decrease in nursing staff utilization with potential for significant cost savings and more efficient use of facility, space, and nursing staff (13).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that major complications after PLB occur in 0-4.6% of pediatric patients [1,2,6,[8][9][10], and that younger age and hepatoblastoma or hepatocellular carcinoma were associated with complications following PLB in pediatric patients [6,7]. However, these studies did not consider whether PLB had been performed on native or transplanted liver.…”
Section: Introductionmentioning
confidence: 99%